Hubungan antara Dukungan Sosial Teman Sebaya dengan Kemandirian Belajar Siswa Kelas VIII MTs Negeri 2 Medan - Irawan, Mirza; Harahap, Masdalifah (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study was to determine the "Relationship Between Peer Social Support and Learning Independence of Grade VIII Students at MTs Negeri 2 Medan Academic Year 2022/2023". This study uses a quantitative approach with the correlation method. In this study, the population consisted of 106 students. Sampling in this study used random sampling, which was taken based on the slovin formula, namely as many as 84 students. The data collection technique used in this study was a questionnaire using a Likert scale. The validity of the instrument was obtained by using the product moment correlation formula, while the reliability of the instrument was obtained by using the Cronbach Alpha formula. Test the hypothesis using the Chi Square test with the help of SPSS IMB 25 for windows. The results of the analysis showed an Asymp.sig (2-sided) value of 0.000 for 84 respondents, so that the value of p <0.05, which means that there is a significant correlation between the variables of peer social support and learning independence